Bilateral sagittal split ramus osteotomy using a conventional osteotome-hammer and a magnetic mallet device: An in vitro comparison - Gençer, R. Çağrı; Özel, Abdullah; Uçkan, İbrahim Sina (NLM (Medline), 2023)
OBJECTIVE: The conventional chisel osteotome technique (CCOT) and the magnetic mallet osteotome technique (MMOT) with a newly manufactured custom osteotome tip for the magnetic mallet device (MMD) were compared to determine whether magneto-dynamic osteotomies are as reliable for orthognathic surgery as the conventional method. MATERIALS AND METHODS: A custom osteotome tip compatible with a magnetic mallet device was manufactured. Thirty-two fresh 1-year-old sheep hemi-mandibles were chosen for osteotomy procedures to achieve the most human-like results. Sagittal split ramus osteotomies were performed, and lingual fracture pattern (LFP), basis split pattern (BSS), duration of sagittal split osteotomy, and alveolar inferior nerve injury were investigated macroscopically. RESULTS: Six of the defined fracture schemes were observed out of the 27 lingual split patterns. After LFP and BSS evaluation, the unfavorable fracture counts for MMOT and CCOT are 3 and 4, respectively. The macroscopic nerve damage assessment for both groups is 2 for MMOT and 1 for CCOT. Although the average durations are similar in both groups, the difference between MMOT samples is closer. None above showed a significant difference. CONCLUSIONS: MMOT was evaluated as a reliable alternative to CCOT in bilateral sagittal split ramus osteotomy based on the lingual and basis split patterns, duration, and nerve damage findings.
Keywords: Magnetic Mallet Device; Conventional Osteotome-Hammer; Ramus Osteotomy